Analysis of a mode III interface crack in a piezoelectric bimaterial based on the dielectric breakdown model - Govorukha, Volodymyr; Говоруха, Володимир Борисович; Kamlah, M.; Камлах, М. (Institut für Angewandte Materialien - Werkstoff- und Biomechanik (IAM-WBM), 2020)
A mode III electrically conductive crack between two different piezoelectric materials under the action of anti-plane mechanical and in-plane electric loadings is analyzed. The strip dielectric breakdown (DB) model, which is free from the electric field singularity, is developed for this crack. According to this model, the electric field along a DB-zone situated in continuation of a crack is assumed to be equal to the electric breakdown strength. The DB-zone lengths are found from the condition of a finite electric field at the end point of such a zone. Using special representations of field variables via sectionally analytic functions, an inhomogeneous combined Dirichlet–Riemann boundary value problem is formulated and solved analytically. Explicit expressions for the shear stress, the electric field and the crack faces’ sliding displacement jump are derived. The stress intensity factor is determined as well. The dependencies of the mentioned values on the magnitude of the external electromechanical loading are presented. Проаналізовано електропровідну тріщину режиму III між двома різними п'єзоелектричними матеріалами під дією антиплощинних механічних та площинних електричних навантажень. Для цієї тріщини розроблена модель смугового діелектричного пробою (БД), яка не має особливості електричного поля. Згідно з цією моделлю, електричне поле вздовж зони БД, розташованого в продовж тріщини, приймається рівним силі електричного пробою. Довжини зони DB знаходять з умови скінченного електричного поля в кінцевій точці такої зони. За допомогою спеціальних подань змінних поля через секційно-аналітичні функції формується та аналітично вирішується неоднорідна комбінована гранична задача Діріхле - Рімана. Явні вирази для напруги зсуву,отримано електричне поле та стрибок ковзного зміщення граней тріщини. Також визначається коефіцієнт напруженості напруги. Представлено залежності згаданих значень від величини зовнішнього електромеханічного навантаження.
Аналіз тріщини інтерфейсу режиму III у п’єзоелектричному біматеріалі на основі моделі діелектричного пробою
Keywords: Piezoelectric materials; П'єзоелектричні матеріали; Interface crack; Тріщина інтерфейсу